Lewis acid molten salts prepared Ti₃C₂Cl₂ MXenes assembling with g-C₃N₄ nanosheets for enhanced photocatalytic H₂ evolution - Zhou, Hongmiao (2023)
Photocatalytic hydrogen (H2) evolution is expected to be a promising approach to generating a clean energy source (H2) with low carbon emissions, which is vital to solving environmental degradation and energy shortages. The critical challenge to designing highly efficient photocatalysts is the fast recombination of photo-generated carriers; thus, we select Ti3C2Cl2 MXene with excellent metal characteristics to serve as a co-catalyst and combine with g-C3N4. The Ti3C2Cl2/g-C3N4 composites exhibit an enhanced photocatalytic hydrogen evolution activity (maximum 155.9 μmol h−1) while they hardly perform photocatalytic activities. The photoluminescence (PL) spectra shows that Ti3C2Cl2 MXenes help boost the separation of photo-generated carriers of g-C3N4 and finally strengthen the photocatalytic hydrogen evolution performance. The ultraviolet–visible (UV–vis) spectra illustrate that composites perform a strengthened light absorption, which fits well with the results in the hydrogen evolution experiment. Thus, we fabricated a highly efficient photocatalyst through a safer molten salt approach without hydrofluoric acid (HF). We believe this work will offer a safer approach to manufacturing catalysts decorated with MXenes for highly efficient photocatalytic H2 evolution.